The role of PIK3CA gene mutations in colorectal cancer and the selection of treatment strategies - Wang, Haitao; Tang, Rui; Jiang, Ling; Jia, Yingtian (Frontiers in Pharmacology, 2024)
PIK3CA gene encodes the p110α catalytic subunit of PI3K, which regulates the PI3K/AKT/mTOR signaling pathway. PIK3CA gene mutation is one of the most common mutations in colorectal cancer (CRC), affecting about 15-20% of CRC patients. PIK3CA gene mutation leads to the persistent activation of the PI3K/AKT/mTOR signaling pathway, which promotes the proliferation, invasion, metastasis, and drug resistance of CRC. This article provides a summary of the key detection methods for PIK3CA gene mutation, and provides an introduction to the existing colorectal cancer treatments and their practical applications in the clinic. Besides, this article summarizes the role and mechanism of PIK3CA gene mutation in the occurrence and development of CRC. It also explores the relationship between PIK3CA gene mutation and the clinical features and prognosis of CRC. This article focuses on the influence and mechanism of PIK3CA gene mutation on the targeted therapy and immunotherapy of CRC, and discusses the potential value and future direction of PIK3CA gene mutation in the personalized therapy of CRC. We aim to provide new perspectives and ideas for the precise diagnosis and treatment of CRC.